Imprisonment of opioid-dependent people in New South Wales, Australia, 2000-2012: A retrospective linkage study - Degenhardt, L.; Larney, S.; Gisev, N.; Trevena, J.; Burns, L.; Kimber, J.; Shanahan, M.; Butler, Tony; Mattick, R.; Weatherburn, D. (2014)
Objective: There are few data about the incarceration of opioid-dependent people involving large representative cohorts. We aimed to determine the prevalence and duration of incarceration in a large cohort of opioid-dependent people in Australia using data linkage methods, and estimate the costs associated with their incarceration. Method: Retrospective linkage study of all entrants to opioid substitution therapy (OST) for the treatment of opioid dependence in NSW, 1985-2010, with data on incarceration, 2000-2012. The number and duration of incarcerations were calculated. The average daily cost of incarceration was applied to days of incarceration in the cohort. Results: Among 47,196 opioid-dependent people, 37% (43% of men and 24% of women) had at least one episode of incarceration lasting one or more days. Men had a median of three (ranging between 1-47) incarcerations, and women, two (1-35). Indigenous men spent 23% of follow-up time incarcerated, compared with 8% for non-Indigenous men; similarly, Indigenous women spent a substantially greater proportion of time incarcerated than non-Indigenous women (8% vs. 2%). Costs of incarceration of this cohort between 2000 and 2012 totalled nearly AUD$3 billion. Conclusions: This is the first study to examine incarceration of opioid-dependent people across an entire population of such users. Our findings suggest that a substantial minority of opioid-dependent people experience incarceration, usually on multiple occasions and at significant cost. Treatment for opioid dependence, inside and outside prisons, may help reduce incarceration of this cohort. © 2013 The Authors. ANZJPH © 2013 Public Health Association of Australia.